Reporting bias in survey data - Yang, Sha (Henry Stewart Talks, 2010)
Survey method, A general modeling framework, Longitudinal panel survey data, The challenge, The proposed model, Modeling true behavior, The HB estimation framework, Include state dependence, The other model parameters, Simulation based on cross sectional data, An empirical application, Possible extensions